Handbook of vegetable preservation and processing / Y H Hui; E Özgül Evranuz - Hui, Y. H.edited by
The second edition of a bestseller, Handbook of Vegetable Preservation and Processing compiles the latest developments and advances in the science and technology of processing and preservation of vegetables and vegetable products. It includes coverage of topics not found in similar books, such as nutritive and bioactive compounds of vegetables; vegetable flavors and sensory properties; genetic engineering; vegetable pests and diseases; active and intelligent packaging; additives and preservatives; quality preservation and/or improvement; computer and control applications; specialties like winter squash and pumpkin, seed sprouts and shalgam; GAP and food safety, among others.